Evaluation of Business Model of E-Wallets of Nepal - Dhakal, Ghan Shyam (Adhyayan Journal, 2023)
This article is intended to evaluate business model elements adopted by Nepalese e-wallets and to find out weak points in its implementation. This article also suggests ways to reduce any loss through which they are running through proper mathematical interpretation. Grey-TOPSIS method is a mathematical interpretation tool that can be used to analyze raw data. The limitation of this research is that it is based on costumer’s opinion rather than being based on company’s data. Though the output of result may vary from one costumer to another, sample population taken into consideration in research have shown that the reason behind loss of e-wallets is lack of proper identification of revenue stream by entrepreneurs. Besides revenue streams, e-wallets should also prioritize their focus on their key activities, customer segmentation, key resources, value proposition, cost structure, key partners and external relationships respectively. The success of e-wallets is not far away if they prioritize their activities as per these findings.